Uji Efektivitas Antioksidan Moisturizer Ekstrak Daun Randu (Ceiba Pentandra (L.) Gaertn.) dengan Metode DPPH - Muadifah, Afidatul; Tilarso, Dara Pranidya; Putri, Amalia Eka; Sowe, Momodou Salieu (Chempublish Journal, 2024)
Dry skin can often cause psychological discomfort. Moisturizer is a preparation that is used to improve dry skin. Kapok plant (Ceiba pentandra L. Gaertn) can be used as an active ingredient of moisturizer and can be used as a treatment, where the chemical content in kapok leaves are flavonoids, saponins, alkaloids, phenolic compounds, tannins and terpenoids as antioxidants. This study aims to determine the antioxidant activity of kapok leaf extract and moisturizer preparations with DPPH method using UV-Vis spectrophotometer, physical quality of preparations and antioxidant activity of moisturizer preparations using DPPH method. Kapok leaf extract was made in various concentrations, namely 20 ppm, 40 ppm and 60 ppm. The IC50 value of kapok leaf extract is 67.4007 ppm which has strong antioxidant activity. Then variations in the concentration of kapok leaf extract were put into the formulation of moisturizer preparations, the results of moisturizer preparations of kapok leaf extract and vitamin C met the requirements of the physical quality test. The moisturizer preparation was continued and tested for antioxidant activity using the DPPH method with ascorbic acid as a comparison. The results of the IC50 value on the kapuk leaf extract moisturizer preparation are 110.065 ppm which is classified as having moderate antioxidant activity and while the vitamin C moisturizer preparation is 9.8417 ppm which is classified as having very strong antioxidant activity.